2024
DOI: 10.1001/jamaoncol.2023.4508
|View full text |Cite
|
Sign up to set email alerts
|

Vaginal Estrogen Therapy Use and Survival in Females With Breast Cancer

Lauren McVicker,
Alexander M. Labeit,
Carol A. C. Coupland
et al.

Abstract: ImportanceGenitourinary syndrome of menopause can be treated with vaginal estrogen therapy. However, there are concerns about the safety of vaginal estrogen therapy in patients with breast cancer.ObjectiveTo determine whether the risk of breast cancer–specific mortality was higher in females with breast cancer who used vaginal estrogen therapy vs females with breast cancer who did not use hormone replacement therapy (HRT).Design, Setting, and ParticipantsThis cohort study analyzed 2 large cohorts, one each in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(3 citation statements)
references
References 14 publications
0
3
0
Order By: Relevance
“…Another cohort study from the UK with 49,237 females with breast cancer and a median duration of follow up of eight years reported no evidence of higher breast cancer-specific mortality in those who used vaginal oestrogen therapy after breast cancer diagnosis (n=2551, 5%) compared with those who did not, including women taking aromatase inhibitors. 25 Similarly, a Swedish case-control study showed no increase in breast cancer-specific mortality in patients with breast cancer who used oestrogen concurrent with tamoxifen and aromatase inhibitors. 26 Although reassuring, neither study reported on breast cancer recurrences and the follow-up times were short to report on early breast cancer mortality.…”
Section: Safety Of Vaginal Oestrogens In Women With Breast Cancermentioning
confidence: 98%
“…Another cohort study from the UK with 49,237 females with breast cancer and a median duration of follow up of eight years reported no evidence of higher breast cancer-specific mortality in those who used vaginal oestrogen therapy after breast cancer diagnosis (n=2551, 5%) compared with those who did not, including women taking aromatase inhibitors. 25 Similarly, a Swedish case-control study showed no increase in breast cancer-specific mortality in patients with breast cancer who used oestrogen concurrent with tamoxifen and aromatase inhibitors. 26 Although reassuring, neither study reported on breast cancer recurrences and the follow-up times were short to report on early breast cancer mortality.…”
Section: Safety Of Vaginal Oestrogens In Women With Breast Cancermentioning
confidence: 98%
“…More recently, a large cohort study has evaluated a total of 49,237 early BC patients, of which 5 % received VaHT and about 1 % received SyHT. In this study, the use of VaHT was not associated with an increased risk of BC-associated mortality (HR 0.57; 95 % CI 0-34-0.96), irrespective of the duration of the exposure or the dosage of estrogens contained in the preparations [ 45 ]. Thereby, the consideration of employing low-dose vaginal estrogens to alleviate GSM in early BC patients could be contemplated, particularly given their proven clinical benefits after unsuccessful non-hormonal strategies.…”
Section: Introductionmentioning
confidence: 99%
“…Local MHT is used for vulvovaginal and genitourinary symptoms. Although not as potent as systemic MHT, it improves the quality of life in a substantial proportion of patients and may also be used also in patients with breast cancer history with certain limitations 7 , 8 .While increased breast cancer risk with menopausal hormone therapy (MHT) is well known 9 , there is some evidence of a reduction in overall mortality among MHT-users 10 . The association between prediagnostic MHT use and cancer-specific and all-cause mortality among breast cancer patients has been found to be favorable compared to non-MHT users in most cohort studies, although results have been variable 11 18 .…”
Section: Introductionmentioning
confidence: 99%